2011
DOI: 10.3382/ps.2011-01570
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evaluation of carcass composition and fat deposition in Japanese quail

Abstract: Current research was conducted to estimate heritability and genetic correlations for carcass composition and fat deposition in Japanese quail at 42 and 91 d of age. Studied traits were BW at 42 and 91 d of age (BW42, BW91), carcass weight and percentage, breast meat weight and percentage, thigh weight and percentage, abdominal fat weight and abdominal fat percentage (AFP), skin weight and skin percentage (SP) as a measure of subcutaneous fat, and the percentage of breast intramuscular fat (IFP). Genetic parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
22
7
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 38 publications
12
22
7
3
Order By: Relevance
“…Sex differences for carcass traits in Japanese quail have been reported previously (Lotfi et al, 2011). However, the present results contrast with the results of other studies that have reported higher carcass percentage in males compared with females in Japanese quail (Minvielle et al, 2000;Vali et al, 2005;Saatci et al, 2006;Shokoohmand et al, 2007;Khaldari et al, 2010;Narinc et al, 2010).…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…Sex differences for carcass traits in Japanese quail have been reported previously (Lotfi et al, 2011). However, the present results contrast with the results of other studies that have reported higher carcass percentage in males compared with females in Japanese quail (Minvielle et al, 2000;Vali et al, 2005;Saatci et al, 2006;Shokoohmand et al, 2007;Khaldari et al, 2010;Narinc et al, 2010).…”
Section: Discussioncontrasting
confidence: 85%
“…Significant hatch effects on carcass traits have been reported by Peebles et al (1999) and Zerehdaran et al (2004) in broilers and Lotfi et al (2011) in Japanese quail. In all of these studies, the mean values of traits in the first hatch were generally lower than later hatches.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The heritability estimate for AF (0.80±0.08) was also high, indicating that this trait can respond very well to selection. Chen et al (2008) worked with Beijing-You birds and obtained a heritability estimate of 0.62, close to those reported in the present study, whereas Lotfi et al (2011), while studying quails, found heritability estimates of 0.28±0.06 for AF, different from those obtained here.…”
Section: Resultscontrasting
confidence: 50%
“…Abdominal and subcutaneous fat are regarded as the main sources of waste in the slaughterhouse. In poultry, high genetic correlations were observed between abdominal fat weight and subcutaneous fat, while there were almost no genetic correlations between abdominal fat weight and intramuscular fat percentage (Zerehdaran et al 2004;Lotfi et al 2011). Selection for reduced abdominal fatness and/or increased breast muscle yield should be effective as both traits were found to be highly heritable and favourably correlated (Ikeobi et al 2002;Jennen et al 2004;Chabault et al 2012).…”
Section: Introductionmentioning
confidence: 99%